Archbishop Francis Redwood : his contribution to Catholicism in New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in History at Massey University - Simmons, Nicholas Anthony (Massey University, 1981)
Unspectacular and evolutionary - these two words sum up the general picture of New Zealand religious history in its present state. This is hardly surprising in that the span of our history has been marked by the growth of secularism. Religion was not the prime motive for migration to New Zealand, as it was for many of the first English immigrants to the United States of America. Our forefathers came seeking financial reward in an "antipodean utopia" that had an economic rather than religious base. But, the plain flavour of New Zealand religious history is also due to a lack of research and writing in the field. No church in New Zealand has had its story told in a way that does it justice. Several church histories have been written but they are either dated or incomplete. However, these books provide a start to a field of historical endeavour that should be exploited in the future. Our religious history has had several figures that have provided spark, like Bishops Selwyn and Moran, or even notoriety as in the case of the Reverend Howard Elliott. A fruitful track in studying our religious history would be a closer examination of the leading figures to see what they said and did, and the impact they had. This thesis seeks to do this, having as its subject Archbishop Francis Redwood, the second Catholic Bishop of Wellington. It is my contention that he did more than any other in transforming the Catholic Church in New Zealand from its missionary state to the institutional type we know today.
Keywords: Redwood, Francis, Metropolitan of New Zealand, 1839-1935; Catholic Church -- New Zealand; Bishops -- Biography; History